Nature around the Palace: Flora and Fauna — the 15th Peterhof Research-Practical Conference: A Survey of Papers - Liashko, Anna V.; Skvortcova , Ekaterina A. (Actual Problems of Theory and History of Art, 2024)
The paper offers a survey of the papers presented at the conference “Nature [around] the Palace” which was held in Peterhof on October 21st‒22nd, 2024. The event celebrated the completion of a large-scale project, i.e. the restoration of the Upper Garden. Saint-Petersburg State University was a co-organizer of the conference. The primary focus was on gardening as an economic phenomenon. The attention was focused on utilitarian structures, such as conservatories, aviaries, and fisheries. Many papers addressed questions of historical assortment of flowers and plants in gardens and in palace interiors, problems of the greening of Saint-Petersburg and its suburbs and preservation of its historical image under conditions of climate warming. Unique for the museum conferences on gardens was the emphasis on fauna. More traditional aspects of museum conferences on gardens were also represented, such as: problems of restoration, history of the lost and damaged monuments, garden as a decoration for theatrical performances, and the symbolism of the gardens.
Keywords: State museum-reserve Peterhof; Saint-Petersburg State University; conference; garden; farm; conservatory; fauna